Environmental and Genetic Risk Factors of Congenital Anomalies: an Umbrella Review of Systematic Reviews and Meta-Analyses - Kyung‐Shin Lee; Yoon‐Jung Choi; Jinwoo Cho; Hyunji Lee; Heejin Lee; Soo Jin Park; Joong Shin Park; Yun‐Chul Hong (2021)
The prevalence of congenital anomalies in newborns in South Korea was 272.9 per 100,000 in 2005, and 314.7 per 100,000 in 2006. In other studies, the prevalence of congenital anomalies in South Korea was equivalent to 286.9 per 10,000 livebirths in 2006, while it was estimated 446.3 per 10,000 births during the period from 2008 to 2014. Several systematic reviews and meta-analyses analyzing the factors contributing to congenital anomalies have been reported, but comprehensive umbrella reviews are lacking.